Local wisdom in the traditional game PÈRÈPÈT JÈNGKOL as strengthening the character of elementary school students - Rahmawati, Agustina; Sylviani, Amelia; Anisah, Anisah; Tarmidzi, Tarmidzi; Putri, Dian Permana (Universitas Tanjungpura, 2025)
The aim of this research is to determine students' character using the traditional game media pérèt jèngkol. This research is descriptive research that uses case studies. This game was played for 6 days (6 meetings) and researchers used observation sheets and videos to